1986
DOI: 10.2307/1541386
|View full text |Cite
|
Sign up to set email alerts
|

ISOLATION AND SEQUENCE ANALYSIS OF A PIGMENT-DISPERSING HORMONE FROM EYESTALKS OF THE CRAB,CANCER MAGISTER

Abstract: The application of separation procedures, including liquid partition, gel nitration, ion-exchange chromatography, partition chromatography, and reversed-phase highperformance liquid chromatography, enabled the purification of an octadecapeptide pigment-dispersing hormone (PDH) from powdered lyophilized eyestalks of the crab, Cancer magister. Automated Edman degradation, followed by the identification of carboxyl-terminal amide, established the sequence of the peptide as: Asn-Ser-Glu-Leu-Ile-Asn-Ser-Ile-Leu-Gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Uca pugilator NSELINSILGLPKVMNDA-NH 2 (Rao et al ., 1985) Cancer magister NSELINSILGLPKVMNDA-NH 2 (Kleinholz et al ., 1986) Callinectes sapidus NSELINSILGLPKVMNDA-NH 2 (Mohrherr et al ., 1990) Orconectes immunis NSELINSILGLPKVMNEA-NH 2 (Rao and Riehm, 1993) Penaeus aztecus NSELINSLLGIPKVMNDA-NH 2 (Rao and Riehm, 1993) Pandalus borealis NSGMINSILGIPRVMTEA-NH 2 (Rao and Riehm, 1993) Insect (PDF)…”
Section: Crustacean (Pdh)mentioning
confidence: 99%
“…Uca pugilator NSELINSILGLPKVMNDA-NH 2 (Rao et al ., 1985) Cancer magister NSELINSILGLPKVMNDA-NH 2 (Kleinholz et al ., 1986) Callinectes sapidus NSELINSILGLPKVMNDA-NH 2 (Mohrherr et al ., 1990) Orconectes immunis NSELINSILGLPKVMNEA-NH 2 (Rao and Riehm, 1993) Penaeus aztecus NSELINSLLGIPKVMNDA-NH 2 (Rao and Riehm, 1993) Pandalus borealis NSGMINSILGIPRVMTEA-NH 2 (Rao and Riehm, 1993) Insect (PDF)…”
Section: Crustacean (Pdh)mentioning
confidence: 99%
“…The major form of this hormone from Pandalus borealis (Fernlund, 1976), identified as an octadecapeptide (DRPH, a-PDH), was shown to elicit pigment dispersion in chromatophores and light-adaptational eye pigment movements (Kleinholz, 1975;Josefsson, 1983). The major form of PDH from brachyuran decapods such as Uca pugilator , Cancer magister (Kleinholz et al, 1986), and Callinectes sapidus (Mohrherr et al, 1990), has been identified as p-PDH.…”
Section: Discussionmentioning
confidence: 99%
“…and designated as P-PDK has been identified as the major form in the eyestalks of the fiddler crab, Uca pugilator . An identical P-PDH (Asn-Ser-Glu-Leu-Ile-Asn-Ser-Ile-Leu-Gly-Leu-Pro-Lys-Val-Met-Asn-Asp-Ala-NH2) is present in other crab species: Cancer magister (Kleinholz et al, 1986) and Callinectes sapidus (Mohrherr et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Brachyuran crabs show the opposite response to Caridea, and their dark chromatophore pigments aggregate in the absence of a pigment‐dispersing hormone (PDH) (Lambert and Fingerman, ; Kulkarni and Fingerman, ). This octadecapeptide exists as two isoforms, α‐PDH (Asn‐Ser‐Gly‐Met‐Ile‐Asn‐Ser‐Ile‐Leu‐Gly‐Ile‐Pro‐Arg‐Val‐Met‐Thr‐Glu‐Ala‐NH 2 ; Fernlund, ,; Josefsson, ), and β‐PDH (Asn‐Ser‐Glu‐Leu‐Ile‐Asn‐Ser‐Ile‐Leu‐Gly‐Leu‐Pro‐Lys‐Val‐Met‐Asn‐Asp‐Ala‐NH 2 ; Rao, ; Kleinholtz et al., ; Mohrherr et al., ). Although a role for PDH in pigment dispersion is well known in crabs (Oguro, ; Castrucci and Mendes, ; Rao, ) and isopods (Fingerman, ; Oguro, ; Castrucci and Mendes, ), it is not clear whether PDH induces pigment dispersion in caridean shrimp chromatophores (Tuma et al., ) or if the dispersion mechanism is triggered simply by RPCH uncoupling from its plasma membrane receptor.…”
Section: Introductionmentioning
confidence: 99%